2022
DOI: 10.3390/v14020300
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Tick-Borne Encephalitis in a Roe Deer (Capreolus capreolus L.)

Abstract: Tick-borne encephalitis virus (TBEV) is the causative agent of tick-borne encephalitis (TBE), a severe zoonosis occurring in the Palearctic region mainly transmitted through Ixodes ticks. In Italy, TBEV is restricted to the north-eastern part of the country. This report describes for the first time a case of clinical TBE in a roe deer (Capreolus capreolus L.). The case occurred in the Belluno province, Veneto region, an area endemic for TBEV. The affected roe deer showed ataxia, staggering movements, muscle tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
2
5
0
1
Order By: Relevance
“…This study supplies the first immunohistochemical description of immune cell subpopulation distribution in roe and fallow deer’s spleen and lymph nodes. The localization and distribution of the principal cells of the immune system of these species were similar to that reported in domestic ruminants [ 27 , 28 , 29 ] and in the few studies conducted on secondary hemolymphatic cervid organs like RAMALT and LMN of red deer [ 30 ] and haemal nodes of roe deer [ 20 ]. Similar investigations were also carried out on peripheral lymphoid tissue in many other wild mammalian species [ 31 ], including chamois [ 14 ], raccoon [ 26 ], Iberian lynx [ 32 ], Tasmanian devil [ 33 ], and tammar wallaby [ 34 ] among others.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study supplies the first immunohistochemical description of immune cell subpopulation distribution in roe and fallow deer’s spleen and lymph nodes. The localization and distribution of the principal cells of the immune system of these species were similar to that reported in domestic ruminants [ 27 , 28 , 29 ] and in the few studies conducted on secondary hemolymphatic cervid organs like RAMALT and LMN of red deer [ 30 ] and haemal nodes of roe deer [ 20 ]. Similar investigations were also carried out on peripheral lymphoid tissue in many other wild mammalian species [ 31 ], including chamois [ 14 ], raccoon [ 26 ], Iberian lynx [ 32 ], Tasmanian devil [ 33 ], and tammar wallaby [ 34 ] among others.…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, few studies have been conducted on haemal nodes and pathological tissues from roe deer [ 18 , 19 , 20 ] and fallow deer [ 21 , 22 ] in which the immune system cells have been phenotyped. Furthermore, no commercial antibodies specifically developed against antigens of these species are available.…”
Section: Introductionmentioning
confidence: 99%
“…Samples in this study were tested for CvHV-1 as it is a frequently reported disease in cervids, although with pathological localization mainly occurring at the ocular level [8,9]; BoAstVCH13/Neuro S1, instead, was studied as an emerging pathogen, described in ruminants in association with encephalitis [10]. The recent findings of Da Rold described animals affected by TBE with a moderate, multifocal encephalitis characterized by perivascular cuffs and neuropil of lymphocytes and histiocytes in both grey and white matter similar to the lesions present in some of our samples [11]. In addition, minimal to mild non-suppurative meningoencephalitis referable to BVDV is relatively common in adult cervids [12].…”
Section: Discussionsupporting
confidence: 57%
“…In animals, the virus is rarely pathogenic, and most animals with TBEV-antibodies have no clinical symptoms. Nevertheless, cases with neurological disease in animals such as sheep, goats, horses, monkeys, deer and even dogs have been published [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The virulence of virus in milk or dairy products can last up until 25 days [ 15 ], depending on storage temperature and the viral load [ 25 ].…”
Section: Discussionmentioning
confidence: 99%